The Effect of Learning Model Variations on Student Concentration in Solving Problems: A Comprehensive Study - Budiwanto, Adri; Marheni, Eddy; Ihsan, Nurul; Pranoto, Nuridin Widya; Purnomo, Eko; Zarya, Fiky (Department of Physical Education, Sport, Health and Recreation, 2023)
Problem solving is a prerequisite for one's survival. A person's inability to solve problems will have a direct impact on his life, including students who are faced with various problems both at school and outside school. Weak problem solving of children can have a negative impact on the decisions taken in dealing with problems so that problems are increasingly tangled and even become one of the causes of student failure and juvenile delinquency. This study aims to see the effect of giving two different learning models based on the level of concentration of students in solving problems. This research is a quasi-experimental research with a treatment design by level 2x2 which concerns two factors. The population in this study was all grade XI students of SMA Negeri 1 Bungo which amounted to 254 students. The sampling technique in this study used a simple random sampling technique. Data was obtained using questionnaires with the instruments used were Grid Concentration test and Problem solving inventory. Data were analyzed using two-track ANOVA at significance level α=0.05. The normality test uses the Liliefors test and the Homogeneity Variance test uses the Bartlett test with a significant level of α=0.05. The results of the data analysis showed that: (1) Overall, there are differences in problem-solving abilities between discovery and cooperative learning models (Sig. 0.048 < 0.05) (2) There is an interaction between learning models and concentration in solving problems (Sig. 0.025 < 0.05) (3) In groups that have high concentration, the discovery learning model is more effective than the cooperative learning model (Sig. 0.003 < 0.020) (4) In groups that have low concentration, the discovery learning model does not can differ with the cooperative learning model group (Sig. 0.996 > 0.05).